Indigenous filamentous fungi on the surface of Argentinean dry fermented sausages produced in Colonia Caroya (Córdoba) - Canel, Romina S. (2013)
Some producers of dry fermented sausages use fungal starter cultures with the aim to achieve a desirable surface appearance and avoid the growth of mycotoxigenic fungi. These commercial cultures are mainly composed ofPenicillium nalgiovensebiotype 6. In contrast, in the case of producers who do not use starters, sausages are spontaneously colonized by the house mycobiota, which generally consists of heterogeneous molds corresponding to different genera and species. In this work, the surface mycobiota of dry fermented sausages produced in Colonia Caroya (Córdoba, Argentina) was determined in both summer and winter seasons. All the sausages sampled had been made without the use of surface fungal starters. In the 57 sausages analyzed in the two winter seasons studied (2010 and 2012), we found a total of 95 isolates of filamentous fungi belonging to six genera (Penicillium,Aspergillus,Mucor,Cladosporium,ScopulariopsisandEurotium) and ten fungal species, whereas in the 36 sausages analyzed in the two summer seasons studied (2011 and 2012), we found 89 isolates belonging to five genera (Penicillium, Aspergillus,Mucor,CladosporiumandGeotrichum) and ten fungal species. Although 16 different species were found in both winter and summer seasons, only 2 of them predominated completely.P. nalgiovensewas found in almost 100% of the sausages analyzed, where biotype 4 was the most frequent. This species gives a whitish gray coloration to the sausages. Considering that the factories sampled do not use fungal starter cultures, this predominance is very interesting since mycotoxin production by this fungus has not been reported.Aspergillus ochraceuswas isolated with a frequency of 80–90% in the summer seasons, but in none of the winter samples. The presence of this fungus in sausages produced in the summer was attributed to the high environmental temperatures and the uncontrolled temperature in the ripening rooms during the night. In all cases,A. ochraceuswas responsible for the undesirable yellowish gold color of the casing. This fungus thus causes significant economic losses to the producers of Colonia Caroya during the months of high temperatures.